The Relationship between Knowledge and Personal Hygiene Behavior of Scavengers at the Putri Cempo Landfill Surakarta - Adelia Lisa Andriyani; Rezania Asyfiradayati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The high generation of waste in Indonesia, especially in the city of Surakarta, as well as suboptimal management has the potential to cause environmental pollution and increase the risk of health problems, especially in vulnerable groups such as scavengers at the Putri Cempo Landfill. This study aims to determine the relationship between knowledge and personal hygiene behavior in scavengers at Putri Cempo Landfill Surakarta with an observational design and this cross sectional approach has been carried out in February 2026. The research population was 287 scavengers, with a sample of 162 respondents taken using the purposive sampling technique. The results were obtained through primary data collected using a questionnaire that has been tested for validity and reliability and equipped with observational data. Data analysis was carried out univariate and bivariate using the Chi-Square test with a significance level of p < 0.05. The results showed that in the group of scavengers with low knowledge, most (56.2%) had poor personal hygiene behavior, while in the group with high knowledge, the majority (66.3%) had good personal hygiene behavior. The results of the Chi-Square test found that there was a significant relationship between knowledge and personal hygiene behavior in scavengers at the Putri Cempo Landfill Surakarta (p = 0.007). The conclusion of the research is the need to educate the scavenger community to increase personal hygiene knowledge and maximize the provision of sanitation facilities around the landfill.